2020
DOI: 10.1002/eji.202048764
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to identify Post‐Aire stages of medullary thymic epithelial cell differentiation

Abstract: Autoimmune regulator+ (Aire) medullary thymic epithelial cells (mTECs) play a critical role in tolerance induction. Several studies demonstrated that Aire+mTECs differentiate further into Post‐Aire cells. Yet, the identification of terminal stages of mTEC maturation depends on unique fate‐mapping mouse models. Herein, we resolve this limitation by segmenting the mTEChi(MHCIIhiCD80hi) compartment into mTECA/hi (CD24−Sca1−), mTECB/hi (CD24+Sca1−), and mTECC/hi (CD24+Sca1+). While mTECA/hi included mostly Aire‐ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…TA-mTECs are concordant with clusters 6 and 9, which are separated most likely because of differences in cell cycle phase proportions (Supplementary Figure S2C, D and E). Cluster 2 seemed to contain both Aire + and Aire -TECs (Figure 3B and C) and its average expression level of Aire was lower than that of cluster 1; therefore, it was assigned to Late-Aire mTECs (Ferreirinha et al, 2021).…”
Section: Mtec Composition Was Persistently Disturbed After Irradiationmentioning
confidence: 97%
“…TA-mTECs are concordant with clusters 6 and 9, which are separated most likely because of differences in cell cycle phase proportions (Supplementary Figure S2C, D and E). Cluster 2 seemed to contain both Aire + and Aire -TECs (Figure 3B and C) and its average expression level of Aire was lower than that of cluster 1; therefore, it was assigned to Late-Aire mTECs (Ferreirinha et al, 2021).…”
Section: Mtec Composition Was Persistently Disturbed After Irradiationmentioning
confidence: 97%
“…Moreover, the identification of many of the new progenitors or mature subsets depends so far on complex scR-NAseq approaches, which are incompatible with their isolation for functional analysis. Therefore, there is a need to develop easier methodologies to prospectively identify these populations based on the expression of specific cell-surface markers [16,17,21,22]. Lastly, complementary genome-wide studies have provided valuable insights into the cellular heterogeneity and transcriptomic diversity of human TECs [23][24][25], which appear to mimic in part the data obtained in the mouse models.…”
Section: New Insights On the Development Of Cortical And Medullary Te...mentioning
confidence: 99%
“…It is recognized that mTECs have distinctive (epi)genetic abilities to express TRA, in a process that is partially dependent on Aire and forebrain embryonic zinc finger 2 (Fezf2) [1,2]. Apart from direct control of TRA expression, Aire regulates alternative processes in mTEC function that cooperates to ensure tolerance induction and prevent autoimmunity [22,28,29]. The promiscuous gene expression capacity of mTECs allows them to function as a library of ubiquitous antigens and TRAs, which at a single cell level are presented in an ordered but randomly organized expression pattern [30][31][32].…”
Section: Ctec/mtec: the Yin And Yang Of T-cell Selectionmentioning
confidence: 99%
“…In addition to TRAs, which are extremely important for testing the self-reactivity of thymocytes, studies have shown that several Aire-dependent genes have different functions in mTECs; these genes participate in processes such as the differentiation and maturation of mTECs [ 14 ], interactions of mTECs with thymocytes and dendritic cells [ 15 , 16 ], induction of thymocyte migration within the thymus, apoptosis of mTECs and even the processing of mRNAs (alternative splicing), thus contributing to the expression of TRA isoforms in mTECs [ 1 3 , 5 , 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%